Benefit and risk profile of tofacitinib for the treatment of alopecia areata: a systemic review and meta‐analysis. (10th October 2019) - Guo, L.; Feng, S.; Sun, B.; Jiang, X.; Liu, Y.
Abstract: Background: Recent insights showed the possibility of using JAK inhibitors for the treatment of alopecia areata (AA). Most of the previous articles evaluated the overall efficacy of existing JAK inhibitors rather than evaluating one of them alone. Currently, the benefit and risk profile of tofacitinib for the treatment of AA is still not clear. Objective: To estimate the safety and efficacy of tofacitinib in patients with AA based on summarizing the clinical outcomes. Methods: The systematic review and meta‐analysis was performed according to PRISMA guidelines. ROBINS‐I (Risk of Bias in Non‐randomized Studies‐of Interventions) was used for quality assessment. Results: We enrolled 14 studies including six clinical trials and eight observational studies with 275 patients. The result of meta‐analysis showed that tofacitinib has reasonable effectiveness in patients with AA. The pooled good/complete hair regrowth rate of tofacitinib treating patient with AA was 54.0% (95% CI: 46.3%–61.5%), and the pooled rate of partial response in patients with AA taking tofacitinib was 26.1% (20.7–32.2%). Approximately a quarter of patients had experience of relapse, most of which was reported due to discontinuation of tofacitinib. In terms of toxicity, reported adverse effects included only mild symptoms. Upper respiratory infection, headache and acne were the most common adverse events. Conclusion: Tofacitinib seems to be a promising drug for the treatment of AA with only mild adverse effects. More thorough larger sized randomized clinical trials are required to further assess the safety and clinical efficacy of tofacitinib for the treatment of AA.